PENGGUNAAN MEDIA FILM KARTUN UNTUK MENINGKATKAN KETERAMPILAN MENYIMAK PADA PESERTA DIDIK KELAS IV SDI DANGA KECAMATAN AESESA KABUPATEN NAGEKEO - Andriana Verena Ngura,; Agustina Pali,; Geryani Suryo Moang Kala, (Jurnal Cakrawala Ilmiah, 2024)
This research aims to describe the use of cartoon film media in improving story listening skills in class IV SDI Danga students and describe the improvement in story listening skills after using cartoon film media in class IV SDI Danga students. This type of research is classroom action research. The data analysis technique used is qualitative dan analysis techique. The research results show that the implementation of learning activities has increased. In cycle I the achievement value obtained was 47,36% and cycle II was 100%. Based on the research results, it can be concluded that the use of cartoon film media can improve listening skills in class IV students at SDI Danga.